2018
DOI: 10.1155/2018/5634352
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Socioeconomic, and Psychosocial Factors Associated with Blood Pressure Control and Adherence: Results from a Multidisciplinary Cardiovascular National Program Providing Universal Coverage in a Developing Country

Abstract: Background Limited information exists on blood pressure (BP) control factors and adherence to antihypertensive drug therapy (Rx) in developing countries. Methods Cross-sectional study in randomly selected 992 hypertensive patients under a Chilean national comprehensive Cardiovascular Health Program (CVHP). Association of education, income, diabetes, obesity, physical activity, psychosocial characteristics, smoking, and alcohol abuse with BP control and adherence were evaluated by multivariate logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 29 publications
5
18
1
1
Order By: Relevance
“…The major finding of this study revealed that about two-thirds of the hypertensive patients on antihypertensive treatment had controlled BP. The level of BP control found in this study (63.6%) was relatively comparable with studies from health care in Chilean (59.7%), 39 in USA at different levels of the health system (60%), 40 South Africa (57%), 41 Bhusal et al in India (58.9%), 5 by Sandoval et al in Chile (63.1%) 27 and by Cordero et al in Spain (55.4%). 10 This close similarity in the level of BP control might be due to similarities in the eligibility criteria for the studies as only hypertensive patients on pharmacologic therapy were included.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The major finding of this study revealed that about two-thirds of the hypertensive patients on antihypertensive treatment had controlled BP. The level of BP control found in this study (63.6%) was relatively comparable with studies from health care in Chilean (59.7%), 39 in USA at different levels of the health system (60%), 40 South Africa (57%), 41 Bhusal et al in India (58.9%), 5 by Sandoval et al in Chile (63.1%) 27 and by Cordero et al in Spain (55.4%). 10 This close similarity in the level of BP control might be due to similarities in the eligibility criteria for the studies as only hypertensive patients on pharmacologic therapy were included.…”
Section: Discussionsupporting
confidence: 85%
“…The participants were classified as physically active if they perform a physical exercise for at least 30 minutes per day for at least 5 days per week (≥150minutes per week), otherwise, they were classified as physically inactive. 9,21,27,38 This physical exercise includes work or sports that involve a moderate-intensity activity that causes small increases in breathing or heart rate, such as brisk walking, carrying light loads, cycling, swimming, volleyball, dancing, farming, gardening, and house working. 16,21…”
Section: Behavioral and Other Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic factors impact hypertension control with respect to diagnosis, treatment, and patient's access and longterm adherence to recommended treatment regimens, and studies suggest that patients with lower SES receive fewer preventive services, lower rates of use of evidence-based therapies, and fewer indicated interventions such as coronary angiography and organ transplantation. [12][13][14] The World Health Organization (WHO) Global Action Plan for the Prevention and Control of noncommunicable diseases (NCDs) targets seven major health risk factors, including insufficient physical activity, current tobacco use and raised blood pressure, for reducing premature mortality from non-communicable diseases by 25% by 2025. Despite being one of the strongest predictors of morbidity and premature mortality worldwide, low socioeconomic status was not included among modifiable risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…19 Psychosocial factors seem to be the driving force of the relationships between socioeconomic factors and adherence. 14,16 For example, in a cross sectional study of randomly selected hypertensive patients (N=992) under a comprehensive cardiovascular health program, the associations of education, income, diabetes, obesity, physical activity, psychosocial characteristics, smoking, and alcohol abuse with blood pressure control and adherence were evaluated by multivariate logistic regression. 14 Uncontrolled blood pressure was significantly associated with low family income, high emotional-stress-depression score and sedentary life style, among other factors.…”
Section: Introductionmentioning
confidence: 99%